Correlation between awareness of community pharmacists in Bataan of their dispensing roles and their dispensing service - Nuevas, Jan Patrice L.; Tamayo, Louise Joy N.,​​; Yu, Kathleen Michelle T. (2017)
The role of pharmacists worldwide is continually evolving in terms of scope and complexity. However, dispensing remains to be the core function of pharmacists. In 2015, the Philippine Pharmacists Association, Incorporated developed a manual called the Philippine Practice Standards for Pharmacists (PhilPSP) which contains the minimum standards required of a practicing Filipino pharmacist. Awareness of pharmacists of the dispensing roles provided in the PhilPSP manual is vital in the provision of service to patients or clients. Furthermore, understanding how pharmacists perceive their performance in dispensing service facilitates the determination of strategies that will improve the quality of such service.